2004
DOI: 10.1081/ese-120039371
|View full text |Cite
|
Sign up to set email alerts
|

By-Side Impurities in Chloronaphthalene Mixtures of the Halowax Series: All 12 Chlorobenzenes

Abstract: Total chlorobenzene content of the Halowax mixtures ranged from 1100 to 9800 ng/g. A lower chlorinated Halowax 1031 and 1000 were a several times more contaminated with chlorobenzenes than higher chlorinated Halowax 1001, 1099, 1013, 1014, or 1051. Depending on the type of the Halowax mixture the most contributing amongst of chlorobenzene homologue groups were di-, tetra-, penta-, and hexa-CBz. A dominance and specific profile of 1,4-DiCBz, PeCBz, and HCBz were characteristic to Halowax 1001, 1099, 1013, 1014,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The compositional profile of CBz of Aroclor 1268 is somewhat similar to that reported for some highly chlorinated technical chloronaphthalene formulations such as Halowax 1051 and 1099. [2,3] The compositional profile of CBzs of Kanechlor 600 is also different from those of Chlorofen, Clophen T 64, and Kanechlor 1000. The abundance of more chlorinated homologue groups is somewhat larger.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The compositional profile of CBz of Aroclor 1268 is somewhat similar to that reported for some highly chlorinated technical chloronaphthalene formulations such as Halowax 1051 and 1099. [2,3] The compositional profile of CBzs of Kanechlor 600 is also different from those of Chlorofen, Clophen T 64, and Kanechlor 1000. The abundance of more chlorinated homologue groups is somewhat larger.…”
Section: Resultsmentioning
confidence: 93%
“…[2] For the Halowaxes, depending on the degree of the mixture chlorination, 1,4-DiCBz, 1,2,3,4-TeCBz, 1,2,3,4,5-PeCBz and 1,2,3,4,5,6-HxCBz were the most contributing among the CBzs found. By examing the Halowax formulations, it was concluded that after initial by-side formation of monochlorobenzene, and due to a steric hindrance effect further chlorine atom entering the ring is substituted in para position, i.e., 1,4-DiCBz is formed preferentially, and further PeCBz and HxCBz.…”
Section: Hexachlorobenzenementioning
confidence: 97%
See 3 more Smart Citations